Agricultural value chains: Examples of quiet transformation - Belton, Ben; Ame, Cho; Fang, Peixun; Win, Myat Thida; Mather, David (International Food Policy Research Institute, 2024)
Myanmar’s agricultural value chains1 are often perceived to be traditional and inefficient and to suffer from underinvestment, credit constraints, and inadequate technology. This perception is partly rooted in the legacy of Myanmar’s military socialist government (1962–1988). During this period, most private business was nationalized, agricultural production in the lowlands was brought under a command-and-control system, and the state assumed all responsibility for the provision of agricultural inputs, services such as mechanization, and crop procurement and marketing.